Evaluation of The Effectiveness of Die Casting Machines Using Overall Equipment Effectiveness (OEE) - Eko Tamas Prasetio; Adriyani Oktora (Jurnal Teknologi dan Manajemen, 2024)
PT YKK Zipco Indonesia is a manufacturing company that produces zipper components, namely chains and sliders. The manufacture of slider products goes through several departments, namely die casting, assembling, painting and plating. The process of making slider products begins with the die casting department which carries out the production process using 17 machines. The problem that exists in the die casting department is that the level of productivity is quite low, so an analysis of the effectiveness of the die casting machine is needed. The aim of this research is to evaluate the performance of the production process in order to increase the efficiency and effectiveness of the company as a whole. The method used in this research is overall equipment effectiveness (OEE) and six Big Losses. The Overall Equipment Effectiveness (OEE) method is used to measure the effectiveness of production process machine performance in manufacturing companies using the parameters availability, performance and quality. In OEE there are six big losses which are categorized into 3 main categories, namely quality loss, downtime loss and speed loss. Then an analysis was carried out using the Pareto diagram and fishbone diagram to find the root causes of the problems that occurred. The results of this research, namely the results of OEE calculations on the C – 07 Die Casting machine, obtained an average OEE value of 78.6%. Based on the six big losses calculation, breakdown losses occupy the highest value with a percentage of 23.1%, making it the losses that most influence the value of machine effectiveness.